2022
DOI: 10.3390/geosciences12040172
|View full text |Cite
|
Sign up to set email alerts
|

How Greek Students Perceive Concepts Related to Geoenvironment: A Semiotics Content Analysis

Abstract: In order to design a geoeducation program in the context of the possibilities given to the Experimental Schools of Greece of Lower Secondary Education, teachers identified the need for diagnostically assess students’ understanding of basic concepts of the geoenvironment and particularly the concepts of geodiversity, geoheritage, geoethics and geotourism. In addition, there was a need to apply the educational technique of creating cognitive conflicts in order to promote the scientific perceptions of these conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…Our review revealed a small but increasing volume of documents reflecting the emerging status and interest in geoethical education as a scientific discipline over the years. The records showed a multidisciplinary engagement with geoethics involving different fields, such as geoscience [7,143,145,148,149,159], sustainability [17,144,153,154], geoheritage [52,147,157], geoconservation [142,156], and geoeducation [141,146,[150][151][152]155,158] which is in line with the transdisciplinary nature of geoethics.…”
Section: Summary Of Key Findings From This Reviewsupporting
confidence: 55%
See 4 more Smart Citations
“…Our review revealed a small but increasing volume of documents reflecting the emerging status and interest in geoethical education as a scientific discipline over the years. The records showed a multidisciplinary engagement with geoethics involving different fields, such as geoscience [7,143,145,148,149,159], sustainability [17,144,153,154], geoheritage [52,147,157], geoconservation [142,156], and geoeducation [141,146,[150][151][152]155,158] which is in line with the transdisciplinary nature of geoethics.…”
Section: Summary Of Key Findings From This Reviewsupporting
confidence: 55%
“…Georgousis et al [152] evaluated the comprehension of geodiversity, geoheritage, geoethics, and geotourism among 45 students in a Lower Secondary School in Greece. Employing the cognitive conflict technique, they aimed to foster scientific understandings of these concepts.…”
Section: Descriptive Analysis Of Existing Records In a Nutshellmentioning
confidence: 99%
See 3 more Smart Citations